Pendekatan Hukum dalam Penanganan Korupsi Jabatan: Studi atas Putusan Nomor 37/Pid.Sus-TPK/2023/PN TJK - Ubaidillah, Kodri; Siswanto, Heni; Fathonah, Rini (Universitas Sang Bumi Ruwa Jurai, 2025)
Decision Number 37/Pid.Sus-TPK/2023/PN Tanjung Karang decided the case of official corruption by imposing a principal penalty of imprisonment and a fine, as well as an additional penalty of payment of compensation for state losses, confiscation of assets, and an additional prison sentence if the obligation is not met. The legal approach used emphasizes individual accountability and upholds the principle of restitution in the criminal law system. The judge's considerations in this decision reflect substantive justice through consideration of social, economic, and moral aspects to maintain bureaucratic integrity and prevent corruption. However, the implementation of the decision requires stricter oversight to ensure effective recovery of state losses. This decision serves as an example of the application of comprehensive law in handling official corruption cases